Bantuan Teknis Perencanaan Dinding Penahan Tanah Pada Warga di Area Rentan Longsor - Yogina Lestari Ayu Situmorang; Boy Macklin Pareira Prawiranegara (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
West Bandung Regency is one of the areas that frequently experiences landslides and landslides. Residents of Cililin Village, which is part of it, have concerns that the slope due to open excavation close to residential houses will have the potential for landslides but do not yet understand how to plan appropriate slope reinforcement. This service activity aims to review the stability of the excavation slopes around residents' houses and then plan a retaining wall that meets safe and stable technical rules. A field survey was carried out to measure the slope geometry and observe the situation around the area. Then slope stability modeling is carried out with input of slope geometry and soil property data. From the analysis results, it was obtained that the slope safety factor value was 1,518, exceeding the minimum safety factor of 1.5, so it was considered quite safe. However, this value is considered low considering that Cililin District is at high risk of landslides. Therefore, additional reinforcement of the slopes was made with earth retaining walls made of rock material. Planning for retaining walls is made of 4 types of varying dimensions. The size of the retaining wall varies, from a width of 3-4.5 m, and a height of 5.5 – 7.5 meters according to the height of each trap. From the planned dimensions, the overall safety factor against overturning, shearing and soil bearing capacity exceeds 1.5, the slope is declared safe. It is hoped that this service activity can become a reference for residents in making retaining walls to strengthen structures on similar slopes.